Endoscopic submucosal dissection (ESD) for anal high-grade intraepithelial neoplasia: a case report - Wagner, Andrej; Neureiter, Daniel; Holzinger, Josef; Kiesslich, Tobias; Klieser, Eckhard; Berr, Frieder (Zeitschrift für Gastroenterologie, 2018)
Anal intraepithelial neoplasia (AIN) is a precursor of anal carcinoma. Conventional therapy is based on topical and local ablative approaches. However, the recurrence rates are very high, leading to repetitive treatment sessions and need for long-term surveillance. Endoscopic submucosal dissection (ESD) is an established treatment for malignant early neoplasias of the gastrointestinal tract, especially in the esophagus, stomach, and colorectum. Japanese centers have reported few cases of ESD for early anal carcinoma. We report a case of high-grade AIN diagnosed with magnifying narrow-band imaging and chromoendoscopy that was resected R0 with ESD en bloc.
Keywords: Endoskopische Submukosadissektion; anale intraepitheliale Neoplasie; Resektion